The concept of multiple hormonal dysregulation - Maggio, Marcello; Cattabiani, Chiara; Laurentani, Fulvio; Ferrucci, Luigi; Luci, Michele; Valenti, Giorgio; Ceda, Gian Paolo (Acta Biomedica Atenei Parmensis, 2010)
Aging process is accompanied by hormonal changes characterized by an imbalance between catabolic hormones that remain stable and anabolic hormones (testosterone, insulin like growth factor-1 (IGF-1) and dehydroepiandrosterone sulphate (DHEAS), that decrease with age. Despite the multiple hormonal dysregulation occurring with age, the prevalent line of research in the last decades has tried to explain many age-related phenomena as consequence of one single hormonal derangement with disappointing results. In this review we will list the relationship between hormonal anabolic deficiency and frailty and mortality in older population, providing evidence to the notion that multiple hormonal dysregulation rather than change in single anabolic hormone is a powerful marker of poor health status and mortality.